The ARMA-APARCH-EVT Models Based on HAC in Dependence Modeling and Risk Assessment of a Financial Portfolio - Moutari, Natatou Dodo; Hassane, Abba Mallam; Diakarya, Barro (European Journal of Pure and Applied Science, 2021)
Multivariate modeling of dependence and its impact on risk assessment remains a major concern for financial institutions. Thus, the copula model, in particular Archimedean hierarchical copulas (HAC) appears as a promising alternative, capable to precisely capture the structure of dependence between financial variables. This study aims to widen the sphere of practical applicability of the HAC model combined with the ARMA-APARCH volatility forecast model and the extreme values theory (EVT). A sequential process of modeling of the VaR of a portfolio based on the ARMA-APARCH-EVT-HAC model is discussed. The empirical analysis conducted with data from international stock market indices clearly illustrates the performance and accuracy of modeling based on HACs.
European Journal of Pure and Applied Mathematics, 14(4), 1467–1489.
Keywords: Hierarchical Archimedean copulas; ARMA-APARCH model; extreme values theory; VaR; CVaR; back-testing; CEFORGRIS; Burkina Faso; Joseph Ki-Zerbo University and Ouaga II University